Pastures under pressure - Effects of other land users and the environment - Horstkotte, Tim; Kumpula, Jouko; Sandström, Per; Tømmervik, Hans; Kivinen, Sonja; Skarin, Anna; Moen, Jon; Sandström, Stefan
2022